5-FU-Induced Upregulation of Exosomal PD-L1 Causes Immunosuppression in Advanced Gastric Cancer Patients - Zhang, Min; Fan, Yibo; Che, Xiaofang; Hou, Kezuo; Zhang, Chaoxu; Li, Ce; Wen, Ti; Wang, Shuo; Cheng, Yu; Liu, Yunpeng; Qu, Xiujuan (Frontiers in Oncology, 2020)
Although the cytotoxic chemotherapeutic agent 5-fluorouracil (5-FU) is generally considered to directly kill cancer cells and exert immunostimulatory effects in advanced gastric cancer, accumulating evidence indicates that it upregulates the expression of PD-L1, a representative immune checkpoint blockade molecule involved in negative regulation of the immune response. It was reported that exosomes could transfer functional PD-L1 locally and distantly to suppress the antitumor immune response. However, whether 5-FU alters the expression of exosomal PD-L1 and induces immunosuppression in gastric cancer remains unclear. Herein, we found that 5-FU increased gastric cancer-derived exosomal PD-L1. Importantly, compared with baseline levels, circulating exosomal PD-L1 was significantly upregulated in 21 stage III–IV gastric cancer patients after two, four, and six repeated cycles of fluoropyrimidine treatment (P = 0.009, P = 0.047, and P = 0.023, respectively), accompanied by decreased amounts of IFN-γ, TNF-α, IL-2, IL-6, and GM-CSF (P = 0.014, P = 0.004, P = 0.009, P = 0.031, and P = 0.014, respectively). Additionally, circulating exosomal PD-L1 was increased more significantly in clinical non-responders compared with responders (P = 0.018). Furthermore, exosomal PD-L1 induced apoptosis in Jurkat T cells and inhibited T cell activation in PBMCs, which could be partly reversed by nivolumab. These results suggested that 5-FU-induced upregulation of exosomal PD-L1 causes systemic immunosuppression in advanced gastric cancer following multiple cycles of chemotherapy, especially after two cycles.